기후변화 시나리오의 불확실성을 고려하기위한 로버스트 의사결정 기법의 개발 및 적용 - 전상묵; 정은성; 이상호; 김연주; Jun, Sang-Mook; Chung, Eun-Sung; Lee, Sang-Ho; Kim, Yeonjoo (Journal of Korea Water Resources Association, 2013)
Climate change is expected to worsen the depletion of streamflow in urban watershed. In this study, we therefore considered the treated wastewater (TWW) use as an adaptation strategy and devised a framework to identify prioritized areas for TWW use. An integrated framework that includes hydrological factors as well as social and environmental components were employed to determine the criteria for decision making. Fuzzy theory was employed to consider the uncertainties in the climate change scenarios and the weights of the performance value. All alternatives were evaluated using the fuzzy TOPSIS method. In addition, statistical method and decision making methods under complete uncertainty were used for robust decision making. As a result, ranking the alternatives using the fuzzy TOPSIS method and robust approach such as maximin, maximax, Hurwicz and equal likelihood criterion mitigated the level of uncertainty and ambiguity in each alternative. The finding of this study can be helpful in prioritizing water resource management projects considering various climate change scenarios. 기후변화에 따른 도시하천의 건천화 현상은 앞으로 더욱더 심각해질 것으로 예상되고 있다. 따라서 본 연구에서는 건천화의 적응전략으로서 하수처리수 재이용을 선정하였고 어느 지영기 우선적으로 선정되어야 하는가를 결정할 수 있는 방법을 제시하였다. 평가기준은 수문학적인 요소뿐만 아니라 인문 사회적인 요소도 포함하였다. 평가치와 가중치의 불확실성을 고려하기 위해 퍼지 이론을 사용하여서 기후변화로 인해 변화된 평가치와 평가기준에 대한 가중치의 불확실성을 완화하고자 하였다. Fuzzy TOPSIS 방법을 이용하여 각 대안을 평가하였다. 또 한로 버스트한 의사결정을 위해서 통계적인 기법과 maximin, maximax, Hurwicz, equal likelihood criterion 방법을 사용하였다. 그 결과 Fuzzy TOPSIS를 통한 대안의 순위 선정과 로버스트 의사결정기법을 통해 불확실성과 순위의 애매모호함을 완화시켰다. 본 연구에서 제시한 방법은 하수처리수 재이용의 위치선정 뿐만 아니라 다양한 기후변화 시나리오를 고려한 수자원 사업의 우선순위를 결정하는데 사용될 수 있다.